Approaches and Patterns of Christian Faith: A Study on the Phenomenon of “Cultural Christians” - XIANG Bingguang, (Journal of Research for Christianity in China (JRCC), 2025)
Since the reform and opening-up, China's religious policies have become more lenient, permitting various religious beliefs—severely prohibited during the Cultural Revolution—to resume their activities to a certain extent. This policy has even spurred a rapid boom in religious studies within China, particularly in the field of Christian studies. Some scholars studying Christianity have been labeled “cultural Christians,” forming a unique phenomenon that has sparked significant debate within both religious and academic circles. These scholars approach Christian studies—and even Christian faith itself—through a distinct belief framework that diverges from Western traditions. Within China's unique cultural context and against the backdrop of atheism as a dominant belief system, their work exhibits distinctive characteristics and trajectories.
Keywords: Cultural Christians Faith Traditions Pathways to Faith Individual Confessions